Thrombotic thrombocytopenic purpura with decreased level of ADAMTS-13 activity and increased level of ADAMTS-13 inhibitor in an adolescent - Eun Mi Yang; Dong Kyun Han; Hee Jo Baek; Young Ok Kim; Myung Geun Shin; Hoon Kook; Tai Ju Hwang (Korean Pediatric Society, 2010)
Thrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy characterized by endothelial cell damage, resulting in microangiopathic hemolytic anemia, thrombocytopenia, and various degrees of neurological and renal impairment caused by microvascular thrombi. It is rare in children and frequently follows a fatal course. TTP is divided into 2 types: one is inherited and associated with ADAMTS-13 gene mutations and the other is acquired and associated with anti-ADAMTS-13 autoantibodies. The measurement of ADAMTS-13 activity in plasma, identification of ADAMTS-13 circulating inhibitor, anti-ADAMTS-13 IgG, and ADAMTS-13 gene sequencing are crucial to the diagnosis of TTP. Plasma exchanges are the first-line treatment for acquired TTP, combined with steroids and immunosuppressive drugs. Here, we describe the case of an adolescent patient with TTP, confirmed by decreased level of ADAMTS-13 activity and an increased level of ADAMTS-13 inhibitor, who was successfully treated by plasma exchanges.